MOBILE ABDOMINAL MASS : HINT IN THE DIAGNOSIS OF BOWEL VOLVULUS - HORSAKUL, Pannee (The ASEAN Journal of Radiology, 2023)
A report of patient, developing caecal volvulus after caesarean section and tubal ligation was made. Plain abdomen might be helpful though not done in this case. In retrospective study, findings of mobile hyperechoic mass during ultrasound study is useful in the differentiation of twisted bowel mass from other intraabdominal diseases developing after surgery. Discussion of incidence, etiology, imaging findings, treatment and differential diagnosis of caecal volvulus have been reported.